Protective Effect of Cranberry Extract against Cisplatin-Induced Nephrotoxicity by Improving Oxidative Stress in Mice - Alkhazragy, Baidaa; N. Alshawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2023)
Cranberry (Vaccinium macrocarpon) is a North American natural fruit. consumed as food and used for health promotion and prevention of various diseases. Aim. The present study was designed to evaluate the protective effect of cranberry fruit extract on nephrotoxicity induced by cisplatin in mice by measuring selected oxidative stress markers. Methods. Twenty-eight male albino mice were used in this study. The animals were divided into 4 groups as follows: Group I [Negative Control]/orally-administered normal saline for 7 successive days; Group II [Orally-administered cranberry fruit extract alone (200 mg/kg) for 7 successive days; Group III/Mice IP injection with cisplatin (12mg/kg) on day 7 and; Group IV [Orally-administered cranberry fruits extract for 7 successive days followed by single IP injection of cisplatin on day 7. After euthanization of each animal by diethyl ether (on day 8th), serum and renal tissue samples were collected for analysis. Results. Administration of cranberry fruit extract resulted in a significant decline in serum creatinine level (0.87±0.120) and a significant elevation in renal reduced glutathione level (197.42±62.958) (P<0.05) with the improvement in the histological analysis of renal tissue of mice of Group IV compared to that in cisplatin intraperitoneally-injected Group III mice. Conclusions. Orally-administrated cranberry extract prior to cisplatin exerts a protective effect against nephrotoxicity induced by cisplatin via improving the oxidative stress process in mice.